Representation of the Value of Friendship in the Novel Sahabat Pena Istimewa by Aisya Najwa Kirana Alenty - Maulidiyah, Ajeng Putri Cahyani; Suyatno (Raja Zulkarnain Education Foundation, 2025)
The research aims to represent the value of friendship in the novel Sahabat Pena Istimewa by Aisya Najwa Kirana Alenty. The research method used is qualitative with library data collection techniques. The data source used in the research is the novel Sahabat Pena Istimewa by Aisya Najwa Kirana Alenty. The results of the analysis show that the novel Sahabat Pena Istimewa by Aisya Najwa Kirana Alenty represents the values of friendship through actions, dialogue and relationships between characters. The value of empathy is represented through a caring attitude, providing knowledge, helping others, sharing, providing opportunities, giving advice, feeling emotions and listening attentively. The value of trust is represented through the attitude of keeping secrets and keeping promises. The value of cooperation is represented through mutual cooperation, helping friends and helping each other. The value of loyalty is represented through the attitude of defending, not leaving and faithfully waiting. The value of honesty is represented through the attitude of not lying, admitting shortcomings and admitting mistakes. The conclusion of the research is that the values of friendship in the novel Sahabat Pena Istimewa include the value of empathy, the value of trust, the value of cooperation, the value of loyalty and the value of honesty.